2018
DOI: 10.1016/j.drugalcdep.2018.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of opioid agonist therapy among incarcerated persons with opioid use disorder in Vancouver, Canada

Abstract: Background: Inability to access opioid agonist therapy (OAT) in correctional settings has previously been reported in Vancouver, Canada, and is associated with harms among people with opioid use disorder (OUD), including overdose death. We investigated the prevalence and correlates of OAT utilization within correctional settings among incarcerated persons with OUD in Vancouver. Methods: Data were derived from three prospective cohorts of people who use drugs in Vancouver between 2005 and 2016. Using multivar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 32 publications
(35 reference statements)
1
24
0
Order By: Relevance
“…Further, increased risk of overdose was understood as associated with decreased tolerance as a result of incarceration and was perceived as a signi cant risk following release from prison. Interventions should prioritize harm reduction in the form of OAT during imprisonment to reduce the risk of fatal overdoses due to decreased tolerance 5,7 . Post-incarceration release is a time when relapse can occur and that transition back to community should support connection to harm reduction services and treatment services 12,20 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, increased risk of overdose was understood as associated with decreased tolerance as a result of incarceration and was perceived as a signi cant risk following release from prison. Interventions should prioritize harm reduction in the form of OAT during imprisonment to reduce the risk of fatal overdoses due to decreased tolerance 5,7 . Post-incarceration release is a time when relapse can occur and that transition back to community should support connection to harm reduction services and treatment services 12,20 .…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between recent incarceration and risk of overdose has been well-documented in the literature. Previous research has shown that a large proportion of incarcerated persons around the world, and in Canada speci cally, report a history of substance use 7,8 . In the US, it has been estimated that up to half of incarcerated peoples have a substance use disorder (SUD) 9 .…”
Section: Introductionmentioning
confidence: 99%
“…None detected 11.8 to drug overdose, misuse, and side effects, especially among high-risk individuals [6,7]. Based on this view, an increased interest in the administration of herbal remedies is considered an alternative pharmacotherapy modality for opioid addiction.…”
Section: Discussionmentioning
confidence: 99%
“…These treatments play an effective role in improving opioid abuse/ addiction outcomes [5]. Unfortunately, the utilization of OAT is associated with the high risk of drug overdose, misuse, undesirable side effects, and drug interactions, especially among individuals in correctional settings or the complications of HIV disease [6,7]. Moreover, the effectiveness of OAT is limited by difficulties at all levels of the therapeutic process, such as diagnosis, entry, and persistence of the patients on treatment; it also needs training health care professionals for the treatment and prevention of opioid abstinence syndrome during the therapy [1].…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between recent incarceration and risk of overdose has been well-documented in the literature. Previous research has shown that a large proportion of incarcerated persons around the world, and in Canada specifically, report a history of substance use [ 3 , 4 ]. In the USA, it has been estimated that up to half of incarcerated peoples have a substance use disorder (SUD) [ 5 ].…”
Section: Introductionmentioning
confidence: 99%